The Role of Digital Literacy in Increasing Understanding of the Qur'an among People Islamic Students - Hanik Hidayati; Wibowo Harry Sugiharto (SEAN Institute, 2024)
Digital literacy among Islamic students has an important role in deepening understanding of the Koran. This research uses a literature study method to review the influence of digital literacy on understanding the Al-Qur'an. The results show that digital literacy provides access to quality Koranic information, broadens understanding and tolerance for religious diversity, and strengthens interfaith relations. Digital literacy also helps solve complex social and environmental problems, enriches Islamic knowledge, and develops critical thinking skills. In the educational context, digital literacy can improve the quality of Islamic education, strengthen cooperation between religious communities, and form responsible, fair and ethical individuals. Educators and educational researchers need to pay attention to the importance of digital literacy in supporting the personal, social and professional development of Islamic students in their lives. Thus, digital literacy is a key factor in increasing understanding of the Koran among Islamic students.